Effect of pH on Binary Biopolymeric Beads of Alginate and Gelatin as Adsorbent for Removal of Cu2+ - Jha, Shipra; Dikshit, S.N.; Pandey, G. (Asian Journal of Chemistry, 2011)
Biopolymeric beads of alginate and gelatin were prepared and characterized by dispersion spectrometer and scanning electron micrograph techniques. On to the surface of beads were performed dynamic adsorption studies of Cu2+ ions at fixed pH and ionic strength of aqueous metal ions solutions. The nature of adsorption was quantified in terms of rate constants for absorption. The influence of various experimental parameters such as pH, temperature and chemical composition of biopolymeric beads on adsorption of copper ions was investigated.